1991
DOI: 10.1080/09670879109371601
|View full text |Cite
|
Sign up to set email alerts
|

Comparative observations on the pest and disease incidence and yield losses of Japonica, Indica and Japonica × Indica rices

Abstract: Comparative field observations of pest incidence on five selected varieties each of Japonica, Indica, and Japonica × Indica rice types indicated that tungro incidence was relatively higher on Japonica varieties, while stem borer incidence at heading stage was higher on Indica varieties. No differences in the relative abundance of other pests on these rice types were observed. Insecticide treatment and caging of plants reduced pest incidence on all varieties. Plant growth and yield of insecticide-treated plants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
2
0
0
Order By: Relevance
“…It was found that the japonica types were more resistant to stem borer. This was previously conformed by Pathak (1967), Tantawi (1985) and Bleih et al (1991) who concluded that rice verities belonging to Indica type are more susceptible to stem borer than those belonging to japonica or Indica x Japonica types. Djamin and Pathak (1967) concluded that japonica rices have more silica content than Indica rices.…”
Section: Resultssupporting
confidence: 72%
“…It was found that the japonica types were more resistant to stem borer. This was previously conformed by Pathak (1967), Tantawi (1985) and Bleih et al (1991) who concluded that rice verities belonging to Indica type are more susceptible to stem borer than those belonging to japonica or Indica x Japonica types. Djamin and Pathak (1967) concluded that japonica rices have more silica content than Indica rices.…”
Section: Resultssupporting
confidence: 72%
“…By contrast, the japonica rice genotypes showed the lowest values of infestation. The obtained results are in accordance with those found by Bleih et al,(1991), who reported that rice varieties belonging to indica or indica/japonica sub-species are more susceptible to rice stem borer infestation than those belonging to japonica one. Resistance of japonica rice varieties to the stem borer could be attributed to its higher silica content than indica types.…”
Section: Insect Reactionsupporting
confidence: 92%